Can intraoperative measurement of bone quality help in decision making for cementless unicompartmental knee arthroplasty? - Eckert, Johannes A.; Jäger, Sebastian; Klotz, Matthias C. M.; Schwarze, Martin; Bitsch, Rudi G. (The knee, 2018)
Background - In uncemented total hip arthroplasty (THA), low bone mineral density (BMD) is associated with aseptic loosening. BMD is usually assessed via dual-energy X-ray absorptiometry (DXA) or quantitative computed tomography, which takes time and exposes patients to radiation. Due to its low risk profile, intraoperative measurement of the trabecular stability might be a useful alternative to DXA. - Methods - In 24 human femora, BMD was analysed using DXA at the femoral necks and the knees. Performing the standard Oxford Unicompartmental Knee Arthroplasty (OUKA) implantation procedure, a wingblade (DensiProbe) coupled to a torque probe was used to evaluate the trabecular peak torque. The standard procedure was modified: before the completion of the central peg drill hole, the DensiProbe was inserted into the pre-drilled hole and then turned until a loss of resistance was achieved. The obtained data was then correlated with BMD at the femoral neck as well as the knee. - Results - In all tested regions, a higher peak torque was observed in correlation with a higher BMD. - Conclusions - As demonstrated, the DensiProbe can be a helpful tool to assess the bone quality intraoperatively in OUKA. It can be a valuable decision guidance when faced with choosing between a cemented and a cementless implant. Due to the fact that the central peg hole of the OUKA can be used for the procedure, no additional risk for the patient exists, while the additional work for the surgeon is minimal.